(untitled) (Journal of Shaheed Suhrawardy Medical College, 2024)
Background: The strategic reperfusion early after Myocardial Infarction trial and the French Registry of Acute Anterior ST segment elevation MI suggested that pharmaco-invasive strategy compares favorably with primary percutaneous coronary intervention (PPCI). Objectives: To evaluate in hospital clinical outcome of patients with acute anterior ST segment elevation myocardial infarction undergoing Primary PCI and pharmaco-invasive PCI. Methods: This cross sectional study was conducted in United Hospital, Dhaka. A total of 120 patients were studied. These patients were categorized into two groups. Those with acute anterior ST segment elevation MI who underwent primary PCI was denoted as group A (n= 55) and those with acute anterior ST segment elevation thrombolysed by streptokinase followed by PCI confined to pharmaco-invasive PCI was denoted as group B (n=65). Results: Acute LVF was more in pharmaco-invasive group than in primary PCI group and was statistically significant (p= 0.032). 02 patients (3.6%) died in primary PCI group: one of which was due to ventricular fibrillation followed by asystole 3 hours after procedure and the other died due to cardiac arrest 10 hours after the procedure. No major bleeding incidence was found in both groups. Conclusion: Acute anterior ST segment elevation myocardial infarction patients receiving pharmaco-invasive treatment compared with the Primary PCI had higher incidence of acute LVF and no significant discrepancy was observed regarding bleeding events, death, stent thrombosis, arrythymia, heart block and cardiac arrest. J Shaheed Suhrawardy Med Coll 2023; 15(1): 34-38